Evaluation of the Implementation of a 25-Year Outdoor School Ground Smoking Ban: A Qualitative Interview Study With Implications for Prevention Practise - Kvillemo, Pia; Feltmann, Kristin; Elgán, Tobias H.; Gripenberg, Johanna (Frontiers in Public Health, 2021)
Introduction: Tobacco use, often initiated in younger ages, is a serious health challenge worldwide. In Sweden, smoking has been prohibited on school grounds since 1994. Municipal environmental and health inspectors control the compliance of the ban. Nevertheless, the enforcement and maintenance of the ban are inadequate. The aim of the current study was to identify facilitators, barriers, and the potential for improved implementation of a 25-year outdoor school ground smoking ban in upper secondary schools. Materials and Methods: A process evaluation was conducted using semi-structured interviews with principals in upper secondary schools, local environmental and health inspectors, and local politicians (n = 30) in Stockholm County, with purposive sampling for informant recruitment. A qualitative content analysis of the transcribed interviews was performed. Results: Three main categories and 10 subcategories were generated from the interviews, revealing facilitators, barriers, and the potential for improvement of the implementation of the ban. A prominent facilitator of the ban was informed and engaged principals and inspectors. Prominent barriers were conflicting goals governing the schools, which reduce staffs' motivation to maintain the ban, unclear school ground boundaries, and lack of resources. Potential for improvement was found in a new tobacco act with an extended ban on smoking at school entrances, extended support for schools and staff to strictly enforce the ban, and a continued denormalisation of smoking in society. Conclusion: To achieve effective implementation of outdoor school ground smoking bans in upper secondary schools, authorities need to address conflicts between different goals governing the schools and give necessary support to the staff to strictly enforce the ban. Policies on smoke-free working hours in the municipalities along with tobacco restrictive policies in the surrounding society may increase the possibility to maintain the smoking ban in upper secondary school grounds.